Re-thinking Eating Disorders as Cultural Pathologies in Contemporary Irish Poetry: A Case Study - Luz Mar González-Arias (Revista Alicantina de Estudios Ingleses, 2024)
Eating disorders—a generic term that includes anorexia nervosa, bulimia, binge eating and many other subtypes of problematic relationships with food and eating—are situated at the interface of disciplines as varied as medicine, biology, history, cultural studies, gender studies and the social sciences. Although the reasons behind the development and experience of an eating disorder are individual as well as cultural, these pathologies tend to be analysed from either an exclusively biomedical perspective—which often excludes the cultural factor—or oversimplified as being the result of the stereotypes of beauty imposed on the female body in western cultural traditions. This essay, in contrast, looks at eating disorders as multi-layered metaphors of cultural dissidence within the social order and literary traditions of contemporary Ireland. It is divided into distinct, though interrelated, sections: a brief introduction to eating disorders; a consideration of the problems posed in the representation of emaciated corporealities; a taxonomical classification of the primary sources found in the course of my research; and the analysis of Mary O’Donnell’s poem “Reading the Sunflowers in September” as a case study to illustrate the literal and metaphorical employment of anorexia in contemporary Irish poetry. Although the análisis is philological, the perspective adopted is that of the Medical Humanities, in that I will make use of literary, cultural and biomedical literature in order to provide a view that is complementary to the scientific discourse around anorexia nervosa. O’Donnell’s poem will be considered in relation to European visual arts, particularly photography, in order to enhance the transnational dimension of eating disorders. At the same time, the close reading of the poem under analysis will be complemented by a comparative analysis with other Irish poems of the late 20th and early 21st centuries to underline the relevance of the national context in interpreting the representation of this disease. Ultimately, this essay aims to proffer new perspectives on the pathology and to contribute to the social understanding of those who experience it.